Associations of socioeconomic status and healthy lifestyle with incident early-onset and late-onset hypertension: a nationwide prospective cohort study in the UK - Siying Liu; Tingting Liu; Di Teng; Haoyu Wang; Fei Li; Cihang Lu; Jiahui Guo; Jie Li; Hanyu Wang; Zhihong Wang; Qiqiang Guo; Jing Zhang; et al. (Population Health Metrics)
Abstract Introduction Low socioeconomic status (SES) and unhealthy lifestyle are known risk factors for hypertension, but their impact on early-onset hypertension remains unclear. Methods A nationwide cohort study using UK Biobank data included 128,918 adults. SES was classified as high, medium, or low through latent class analysis of household income, employment, and education. A healthy lifestyle score was based on nonsmoking, moderate alcohol use, physical activity, and diet quality. Early-onset hypertension was defined as diagnosis before age 50; late-onset hypertension was diagnosed at 50 or older. Results Early-onset hypertension incidence was 2.93%, while late-onset was 14.45%. In early-onset hypertension, incidence increased from 2.03% in high SES to 7.35% in low SES (p < 0.001). For late-onset hypertension, incidence ranged from 9.70 to 20.74% (p < 0.001). Medium and low SES were significant risk factors for both forms of hypertension. The mediation effect of a healthy lifestyle on early-onset hypertension was 3.16%, and 0.42% for late-onset. Low SES combined with an unhealthy lifestyle increased early-onset hypertension risk by 356% and late-onset by 105%. The strength of the associations between risk factors for early-onset hypertension was greater than that for late-onset hypertension, particularly for low SES, obesity, and low education level. Conclusions Low SES is a stronger risk factor for early-onset hypertension than late-onset. A healthy lifestyle provides significant protection, especially in low SES groups. Tailored interventions addressing SES, education, and obesity are essential for preventing both early- and late-onset hypertension.